Nghiên cứu điều chế 2-amino-5-cloro-benzophenon nguyên liệu trung gian quan trọng trong tổng hợp thuốc an thần gây ngủ diazepam - Châu và cộng sự, Phan Đình (Vietnam Journal of Chemistry, 2014)
Important intermediate in the synthesis of diazepam is 2-amino-5-chloro-benzophenone (2). It was prepared in fours steps from the chlorobenzene through 4-nitro-chlorobenzene (5), 4-amino- chlorobenzene (6) and 4-(N-benzoylamido)chlorobenzene (7). The structure of all compounds 2, 5, 6, 7 were supported by analitycal and spectroscopic evidences.